Молекулярні механізми негативного впливу метаболічного синдрому на ризик виникнення та прогноз перебігу раку молочної залози у жінок у постменопаузі - Щепотін, І. Б.; Зотов, О. С.; Любота, Р. В.; Любота, І. І. (Clinical Endocrinology and Endocrine Surgery, 2012)
Breast cancer and metabolic syndrome remains one of the most urgent problems of modern medicine worldwide. In this review, highlights the molecular pathways that underlie the negative impact of metabolic syndrome on the risk and prognosis of breast cancer. A better understanding of these pathways will help to optimize prevention and treatment of breast cancer in patients with metabolic syndrome.